Trees on farms: diversity, carbon pool and contribution to rural livelihoods in Kanchanpur District of Nepal - Baral, SK; Malla, R; Khanal, S; Shakya, R (Banko Janakari, 2013)
Trees and shrubs are important component of rural farming system in Nepal. This paper assesses tree diversity and carbon pool of trees and shrubs outside forests as well as their contribution in the rural economy of the study area. In the land use classification map derived from the high resolution ALOS Pan-sharpened imagery, random selection was made among systematic grid in the agriculture class to find out the inventory plot. The plot was designed as nested plot. Firstly, tree measurement was done and then leaves, branch samples as well as soil samples were collected from each sample plot. Structured questionnaire survey was used to assess the contribution of trees and shrubs on rural livelihoods. The biomass and soil samples were analyzed using dry combustion method to estimate the carbon content. The amount of carbon stock difference between farmland with TOF and without TOF was found 26.56 Mg (megagram) ha-1. There was 350,714.6 Mg above ground carbon, 35,103.36 Mg root carbon and 84451.18 Mg soil carbon accumulated by total trees and shrubs on farms in the District. Hence, the total carbon pool of the District in different agroforestry systems was estimated to be 470,269.18 Mg. Homegarden system was found to be a good agroforestry system in terms of having higher species richness, tree diversity and relatively higher amount of above and below ground carbon per unit area. The results also showed that the trees on farms contributed16.4% (NRs. 3689 per household/year) and 17.1% (NRs. 2613 per household/year) of farmland income and livestock income respectively. The results, thus, indicate that trees on farms have visible impacts on rural livelihoods, harboring rich plant diversity and sequestering substantial amount of carbon. Banko Janakari, Vol. 23, No. 1, Page 3-11 DOI: http://dx.doi.org/10.3126/banko.v23i1.9462